Combination Therapy versus Monotherapy in the Treatment of Stenotrophomonas maltophilia Infections: A Systematic Review and Meta-Analysis - Abhisit Prawang; Naphatsawan Chanjamlong; Woranattha Rungwara; Wichai Santimaleeworagun; Taniya Paiboonvong; Thidarat Manapattanasatein; Prompiriya Pitirattanaworranat; Pongsakorn Kitseree; Sukrit Kanchanasurakit (Antibiotics, 2022)
Stenotrophomonas maltophilia is a multidrug-resistant bacterium that is difficult to treat in hospitals worldwide, leading to high mortality. Published data describing the use of monotherapy or combination therapy and which one is better is still unclear. We aimed to investigate the efficacy of monotherapy and combination therapy in the treatment of S. maltophilia infections. We performed a systematic review of combination therapy and additionally a systematic review and meta-analysis to determine the effects of monotherapy versus combination therapy on mortality in S. maltophilia infections. Electronic databases: Cochrane Library, PubMed, Embase, ClinicalTrials.gov, Scopus, and OpenGrey were accessed. Of the 5030 articles identified, 17 studies were included for a systematic review of combination therapy, of which 4 cohort studies were finally included for meta-analysis. We found there is a trend of favorable outcomes with respect to mortality in the use of combination therapy to treat complex or severe S. maltopholia infections. A meta-analysis of monotherapy showed a statistical significance in the decreasing rate of mortality in hospital-acquired pneumonia (hazard ratio 1.42; 95% confidence interval, 1.04–1.94) compared to combination therapy, but not significant in bacteremia (hazard ratio 0.76; 95% confidence interval, 0.18–3.18). Further studies should continue to explore this association.